Analysis of Microstructure Changes for AlSi7Mg0.3 Alloy Caused by Modification - Hren, Iryna; Svobodova, Jaroslava; Michna, Štefan (Manufacturing Technology Journal, 2019)
The aim of this experiment was to investigate the influence of the Sr modifier in the Al-Si eutectic alloy on the structure change and its mechanical properties. For this reason, an Al-Si7Mg0.3 hypoeutectic silumin alloy was modified with the aim of improving the mechanical properties of the material, mainly by increasing the ductility and strength. The subject of investigation was analysis of morphology of excreted eutectic silicon. In order to investigate the surface, metallographic cross-sectional specimens were prepared using light and electron microscopy. A static tensile test was performed for detailed examination. It has been found that the addition of the AlSr10 modifier and, over the time of modification of 1 to 2 hours, has increased the mechanical properties, in particular the ductility.
Keywords: AlSi7Mg0.3; modification; strontium; microstructure